'Water Brought Us Together': A Baptismal Ethic from Flint - Daley Mosier, Kristen (Religions, 2022)
What lessons and insights can the broader Church learn from Christian faith leaders in Flint, Michigan, who have been in a sustained struggle for justice amidst the still unfolding impacts of environmental racism? How did the baptismal identities of faith leaders function as a resource in this struggle, and on a broader level how might Christian baptismal practices and theory be a resource for solidarity in the struggle for racial and environmental justice in and beyond Flint? In other words, might the waters of Christian baptism also “bring together” Christians to tangibly resist racism? This essay emerges from a qualitative research project examining baptismal practices amidst the water crisis in Flint, Michigan. Using liberationist methodology and employing conversation as a means of co-constructing theological knowledge, this article seeks to define a baptismal ethic born from the water crisis based upon the lived experiences of Christian leaders and their communities.